Modeling and experimental verification of an ionized gas barometer. (February 2021) - Stewart, Matthew C.; Jones, John D.; Leung, Albert M.
Highlights: Practical considerations for using ionized gas as a barometer. Modeling of non-linear effects due to ion recombination. Modeling of non-linear effects due to ionizing radiation emission pattern. Experimentally verified ionized gas barometer model. Abstract: A model has been developed and experimentally verified to determine the feasibility of ionizing a gas to measure barometric pressure. Alpha particles emitted from an americium 241 source ionize the gas. The number of ions created depends directly on the number of alpha particle-gas molecule interactions which is proportional to gas pressure. An electric field applied to the ionized gas causes current proportional to the ion count and therefore gas pressure. Several nonlinear effects have been identified and modeled including gas chamber geometry, alpha particle source emission pattern and ion recombination. The lack of any moving components or dependence on material strain leads to resistance to shock and strain. With suitable low power amplification electronics, overall power level of a few μW can be achieved. The cm scale of the sensing element would be the driving factor in the size of a final device.